ANALISIS PERAN PT MITRA LINTAS NUSANTARA JAKARTA SEBAGAI FREIGHT FORWARDER DALAM PENGIRIMAN BARANG MELALUI LAUT CABANG JAKARTA UTARA - Linda Sari Linda Sari; Rame Soekarsono Rame Soekarsono (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study is to find out and benefit from the role of domestic shipping services in shipping goods by sea. Descriptive qualitative research method with data collection techniques through in-depth interviews, observation and documentation. The results of this study are to show that PT Mitra Lintas Nusantara as a freight forwarder company engaged in goods delivery services as well as being responsible for all transportation activities from the beginning to the destination of goods, from domestic to abroad, the country of destination of the exporter. PT Mitra Lintas Nusantara assists shippers or exporters in finding shipping companies that can provide lighter transportation costs or at special prices according to separate classes. The procedure carried out by PT Mitra Lintas Nusantara in shipping export goods by sea is the initial process of receiving Shipping Instructions from the shipper then from the SI it is used for booking space at the shipping agent which will later make a draft Bill of Lading to obtain a Delivery Order, then from PT Mitra Lintas Nusantara begins to take care of custom clearance (customs) documents to obtain PEB (Notice of Export of Goods) after all is completed, on the stuffing date determined by the sender from PT Mitra Lintas Nusantara sending a draft Bill of Lading document to the shipper then just stuffing in the stuffing process it will the container number and seal number are written on the container box, then after everything is finished PT Mitra Lintas Nusantara sends a copy of the Bill of Lading document that has been signed by the manager to the sender as a sign that the transportation is complete.